Effects of a 20-min Nap after Sleep Deprivation on Brain Activity and Soccer Performance - Ajjimaporn, Amornpan; Ramyarangsi, Papatsorn; Siripornpanich, Vorasith (International Journal of Sports Medicine, 2020)
We examined effects of a 20-min nap following 3 h of sleep deprivation on brain wave activity, auditory reaction time, the running-based anaerobic sprint test, leg muscle strength and the rating of perceived exertion in male college soccer players. Eleven players underwent three sleep conditions; normal sleep, sleep deprivation and 20-min nap after sleep deprivation. The sleep deprivation demonstrated an increase in the mean power of delta waves over the frontal area and a decrease in the mean power of alpha waves over the parietal area compared to the normal sleep. The nap and the sleep deprivation showed an increase in auditory reaction time compared with those in the normal sleep. The sleep deprivation demonstrated a decrease in the running-based anaerobic sprint test compared to the normal sleep, whereas the nap has partially reversed only minimal power and average power of the running-based anaerobic sprint test. The nap showed a recovery effect on leg muscle strength, but not on the rating of perceived exertion compared with the sleep deprivation. Thus, a 20-min nap after sleep deprivation did not completely return brain activity back to active state and did not entirely reverse the negative impact of sleep deprivation on soccer performance in soccer players.
Keywords: running-based anaerobic sprint test (RAST); RPE scale; the nap opportunity; auditory reaction time; electroencephalogram (EEG)